Titel prent: De verloopen zaak : Mr. Marchant: "Het is geen wonder dat wij op de flesch moeten..." - Hahn, Albert,
Titel prent: De verloopen zaak : Mr. Marchant: "Het is geen wonder dat wij op de flesch moeten...".